2021
DOI: 10.1186/s12974-021-02238-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 blockade attenuates white matter inflammation and oligodendrocyte loss after progressive systemic lipopolysaccharide exposure in near-term fetal sheep

Abstract: Background Increased systemic and tissue levels of interleukin (IL)-1β are associated with greater risk of impaired neurodevelopment after birth. In this study, we tested the hypothesis that systemic IL-1 receptor antagonist (Ra) administration would attenuate brain inflammation and injury in near-term fetal sheep exposed to lipopolysaccharide (LPS). Methods Chronically instrumented near-term fetal sheep at 0.85 of gestation were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 79 publications
(90 reference statements)
9
39
0
Order By: Relevance
“…Moreover, we observed a reduction in the magnitude of LPS-induced hypoxemia, hypercapnia and acidosis, particularly after the third LPS infusion. This is consistent with previous studies from us and others that have shown tolerance to subsequent LPS doses ( Feng et al, 2009 ; Feng et al, 2010 ; Lear et al, 2014 ; Lear et al, 2015 ; Galinsky et al, 2020a ; Kelly et al, 2021 ). The immune tolerance is in part mediated by reprogramming of the innate immune system as shown by studies in human and sheep monocytes, whereby repeated LPS exposure is associated with decreased cytokine production and downregulation of the LPS receptor CD14 ( Mengozzi et al, 1993 ; Kramer et al, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, we observed a reduction in the magnitude of LPS-induced hypoxemia, hypercapnia and acidosis, particularly after the third LPS infusion. This is consistent with previous studies from us and others that have shown tolerance to subsequent LPS doses ( Feng et al, 2009 ; Feng et al, 2010 ; Lear et al, 2014 ; Lear et al, 2015 ; Galinsky et al, 2020a ; Kelly et al, 2021 ). The immune tolerance is in part mediated by reprogramming of the innate immune system as shown by studies in human and sheep monocytes, whereby repeated LPS exposure is associated with decreased cytokine production and downregulation of the LPS receptor CD14 ( Mengozzi et al, 1993 ; Kramer et al, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed significant reductions in SaO 2 in LPS-exposed fetal sheep over the 3-day experimental period and we have previously reported increased production of pro-inflammatory cytokines, including IL-1β ( Kelly et al, 2021 ). Hypoxia and IL-1ß-induced inflammation rapidly increases microsomal prostaglandin E-synthase 1 (mPGES-1) expression within the rodent brainstem ( Hofstetter et al, 2007 ).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…They can also release inflammatory mediators resulting in microglia activation and express cytokine receptors, promoting microglial recruitment to damage sites [234]. Remarkably, blockade of LPS-stimulated pro-inflammatory molecules decreases oligondendrocytic loss and reduces WM impairment [236].…”
Section: Oligodendrocytes and Neuroinflammationmentioning
confidence: 99%